A Study on Vocabulary Learning for Young Learners in Gwynfor English Course Jombang in The Academic Year of 2021/2022 - Ardiansyah Ardi Ardi (JETAL: Journal of English Teaching & Applied Linguistic, 2022)
This research is based on learning vocabulary in A 1 class of Gwynfor English Course Jombang. Most of students complain that the teaching activities are very boring. Moreover, speaking skills require a lot of practice so that students are fluent in English. vocabulary is a core part of language skills and provides much of the basis for how well students speak, listen, read and write. Many students in Indonesia are difficult to understand English lessons properly, their main obstacle is the lack of vocabulary mastery. The problem of this research how are the teachers make learning English easy to understand and how are the processes of learning vocabulary in Gwynfor English Course Jombang. The researcher uses the descriptive qualitative method. In this study the researcher found some ways that used in by the tutor in teaching vocabulary learning in A 1 class are using songs, games and pictures.